The Carnegie Corporation Advisory Group on Canadian College Libraries, 1930–35 - Bruce, Lorne D. (Historical Studies in Education / Revue d'histoire de l'éducation, 2016)
The Carnegie Corporation of New York (CCNY) contributed signi cantly to the development of Canadian university and college libraries during the Great Depression. From 1932 to 1935, thirty-four institutions of higher education shared in library book grants totalling $214,800 as a result of a national (Canada and Newfoundland) examination conducted by an advisory group established by the CCNY. The ways in which the advisory group investigated and inspected potential recipients, evaluated whether they complied with conditions set, and distributed grants typically followed the policies and procedures established by an earlier American advisory group funded by the CCNY. Carnegie and university records document how nancial aid was awarded and used for the advancement of undergraduate print collections. Sources can also be used to study the Canadian group in relation to the role of American philanthropic college library work, attempts by Canadian administrators to adapt library collections and organization to local circumstances, and trends in the improvement of undergraduate library services on a national scale. RÉSUMÉ L’organisme The Carnegie Corporation of New York (CCNY) a contribué d’une manière signi- cative au développement des bibliothèques des universités et des collèges canadiens durant la grande dépression. De 1932 à 1935, trente-quatre institutions d’éducation supérieure se sont partagé des octrois totalisant 214 800 $ pour l’achat de livres. Ce montant a été établi lors d’une enquête nationale menée conjointement au Canada et à Terre-Neuve par un groupe de travail consultatif établi par le CCNY. Les manières de procéder de ce comité quant à l’inves- tigation et à la surveillance des institutions récipiendaires, l’évaluation du respect des conditions xées ainsi que la distribution des subventions s’appuient sur les politiques et procédures établies précédemment par un comité consultatif américain créé par le CCNY. Les documents provenant de la corporation Carnegie et des universités exposent comment l’aide ...